Kritika islámu na českém internetu – možnosti interpretace: Případ facebookové stránky Islám v České republice nechceme - Havlíček, Jakub (Lidé města, 2015)
This paper is a case study of the criticism of Islam and Muslims in the Czech lands, as shown on the example of the Facebook page Islám v České republice nechceme (“We do not want Islam in the Czech Republic”). Even though the number of Muslims in the Czech Republic is relatively small (probably not exceeding 11,000 individuals), the topic of Islam and Muslims is widely discussed in the public sphere of the Czech society. This paper aims at answering the following questions connected to Islam entering public sphere: what is the context of criticism of Islam in the Czech society? What theoretical tools of social sciences can be applied in analysing, explaining and understanding this criticism of Islam in the Czech environment? The paper provides a brief analysis of posts on the Facebook page Islám v České republice nechceme. It describes and analyses the content and visual aspects of the posts. The administrators of the page are identified as “opinion leaders”. The role of opinion leaders is based on their involvement in a social categorical relationship shared with their followers, connected to the process of defining Czech national identity. This identity is formulated in contrast with “Islam” and “Muslims”. Their characteristics and values are generally presented as contradictory to “Czech cultural values”. The criticism of Islam is interpreted as a case of “moral panics”, and, for its connection to the process of defining Czech national identity, it is also endowed with considerable political potential. The criticism of Islam in the process of defining Czech national identity is connected to the imagery of Muslims in the collective memory of the Czech society.